2004
DOI: 10.1068/a3637
|View full text |Cite
|
Sign up to set email alerts
|

Conservatives and Champions: River Managers and the River Restoration Discourse in the United Kingdom

Abstract: IntroductionEnvironmental restoration is a central rhetorical component of debates about sustainability. Whereas the primary motivation for conservation through the 20th century was to preserve elements of`wild nature' from extinction (Adams, 2003), an allied concern was for the restoration of ecosystems degraded by human action [for example, US prairie habitats destroyed by intensive agriculture (Jordan et al, 1987a) or the rehabilitation of polluted industrial land (Bradshaw, 1987;]. In the 1980s and 1990s r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 15 publications
1
45
0
1
Order By: Relevance
“…We daily encounter an established orthodoxy which promotes an engineering concept of 'stability' (Adams et al 2004). Whilst these authors claim 'The emphasis on the idea of restoration has become part of discursive and practical strategies in environmental planning', they also remind us that 'Restoration champions therefore continue to function within broadly conservative organisations, suspicious of their proposals.…”
Section: Tooling Up Robust Metrics: Uncertain Science and Adaptive Mamentioning
confidence: 99%
“…We daily encounter an established orthodoxy which promotes an engineering concept of 'stability' (Adams et al 2004). Whilst these authors claim 'The emphasis on the idea of restoration has become part of discursive and practical strategies in environmental planning', they also remind us that 'Restoration champions therefore continue to function within broadly conservative organisations, suspicious of their proposals.…”
Section: Tooling Up Robust Metrics: Uncertain Science and Adaptive Mamentioning
confidence: 99%
“…In many cases, this comfortable institutional arrangement persists, with the mind-sets of less progressive planners and engineers proving difficult to change (Moss and Monstadt, 2007). The lack of track record for the new approaches to integrated water management leaves these engineers and planners dismissive or cautious of the new environmental discipline, their ideologies creating mechanisms of path dependency, posing significant barriers and frustrating attempts to innovate from their more progressive colleagues (Adams et al, 2004). As Moss and Monstadt (2007) note, there is mounting 'anecdotal' evidence that it is not local stakeholders who fail to appreciate recent shifts in government policy, but that they are unable to follow policy as they themselves and central government would like.…”
Section: Understanding the Differences In Culture And Contextmentioning
confidence: 99%
“…Based on the river's functions and water quality and considering the opinions of multiple scholars (Wang, 2007;Yang, 2008), the development history of Love River can be divided into five stages: (1) construction of sewers and a floodgate system was carried out; the Love River's scenery regulation plan was formulated. These efforts together with other measures that fit the local conditions drove the transformation of the scenery and space along the river.…”
Section: Research Subject: Love River Of Kaohsiung Citymentioning
confidence: 99%
“…With many issues involved, urban riverbank development is based on the three principles of ecological environment, spatial system, and human psychology, and its planning is carried out in eight aspects, including nature, cleanliness, safety, accessibility, development, history, and regional features (Shi et al, 2009). Past research has shown that the functions and traits of urban rivers could be explored from four angles, including environmental, city, space and human angles (Japan Society of Civil Engineers, 1988; Adams, 2004); the functions of urban rivers and banks include ecological protection, water flow, water control, hydroelectric power generation, disaster prevention, transportation, scenery shaping, provision of activity venues and medical treatment. Human activities along rivers could be classified into eight categories, including rest, sightseeing, performance, sport, transport, local traditional folk events, scenery appreciation and education.…”
Section: Literature Review 21 Functions Of Urban Riverbank Space Andmentioning
confidence: 99%
See 1 more Smart Citation